Desain Bahan Ajar Bahasa Indonesia Berbasis Kearifan Lokal - R, Rostina (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to know the effectiveness of local wisdom-based Indonesian language teaching materials for high school students of grade X. The research method uses the Quest Experiment, with a Pretest-Posttest design Control Group Design uses two groups, namely the experimental group and the control group. Based on hypothesis testing by calculation of independent sample t-test it is known that the mean increase of the experimental group is 21.81, while the increase of the control class is 17.12 so it can be known that the increase in learning outcome score of the experimental class is greater 4.69 compared to the control class. The results of the study showed a thitung value of 0.027 with a significance of The t table value from db 2 is 2.92. So it can be concluded that ttabel thitung (0.027 2.92) and the significance value is less than 0.05 (p = 0.000 0.05). There was a significant difference in the improvement of learning outcome scores significantly in both the experimental group and the control group. Hence, the use of local knowledge-based teaching materials is influential during the learning process.